Russian Federation : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
The Russian Federation economy saw growth of about 4 percent and a current account surplus-the result of favorable harvest, high oil prices, and reduced unemployment and inflation. Implementation of structural reforms initiated by the Central Bank of Russia (CBR), managing domestic demands, and non-vulnerability to oil price variation were suggested by the Executive Board as short and mid-term challenges. Strengthening monetary policy framework, allowing greater exchange rate flexibility, implementing Financial Sector Assessment Program (FSAP) recommendations, expansion of CBR powers, reduced state involvement in the economy, and enhancement of communication policies were also recommended.